Dinâmica de paredes de domínios sob o efeito de correntes elétricas - Beck, Fábio (2013)
In this work, we have measured the domain wall velocity in the low field regime and studied the domain wall dynamics in Joule-annealed amorphous glass-covered microwires with positive magnetostriction. Such microwires are known to present magnetic bi-stability when axially magnetized. In order to measure of the single domain wall dynamics under different conditions, an electrical current was applied to the wire simultaneously to the mechanical stress and driving magnetic field. We have observed that the applied stress decreases the domain wall mobility. When the dc current is applied to the sample, an increase or a decrease is observed on the axial domain wall mobility, depending on the current direction. When we have treated the orthogonal motion of the domain wall, the current influence is not detected. On the other hand, it was verified a modification on the domain wall length. It was also observed a change in the domain wall shape from conical to parabolic one. These results are explained in terms of the change in the magnetic energy promoted by the additional Oersted field which, by its time, modifies the length and shape of the conical domain wall, in such a way that the orthogonal domain wall velocity is not changed by the applied current.